Multiple populations of double-stranded RNA in two virus-harbouring strains of Trichomonas vaginalis - Flegr, J; Cerkasov, J; Stokrová, J (Folia microbiologica, 1988)
The existence of six dsRNA segments of Trichomonas vaginalis virus was confirmed and the molar mass and relative abundance of these segments were determined by agarose gel electrophoresis with reovirus dsRNA serving as a standard. The M's were 3.5, 3.4, 3.2, 2.5, 1.4 and 0.34 Mg/mol for the two strains studied, the relative abundances, however, were 1.0, 1.4, 3.0, 0.3, 2.7, 4.2 and 1.0, 0.6, 1.7, 0.5, 3.4 1.0 for these strains, respectively. Cell homogenate fractionation showed that all dsRNA segments were associated with viral particles. The data appeared to support the hypothesis of a relationship between viruses of the protozoan T. vaginalis and of the yeast Saccharomyces cerevisiae.
Keywords: dvouvláknová RNA; Animals; Trichomonas; RNA, Viral; RNA virová; zvířata; RNA, Double-Stranded